Trichoscopy of Dark Scalp - Ocampo Garza, Jorge; Tosti, Antonella (2018)
Abstract Trichoscopy (dermoscopy of the hair and scalp) is a technique that improves diagnostic accuracy and follow-up with hair and scalp disorders. Although several studies of trichoscopy have been made in Caucasian and Asian populations, little has been published regarding trichoscopy findings in skin of color, despite the great prevalence of hair diseases in populations with this kind of skin. The aim of this review was to describe the trichoscopic features of normal scalp and of hair disorders in patients with dark skin phototypes. This will help dermatologists to distinguish between unique trichoscopic features of dark skin, and allow them to provide more accurate diagnoses and treatments for these patients.